Effectiveness and Clinical Outcomes of Long-Term Rifaximin in Cirrhotic Patients with Hepatic Encephalopathy: Long-Term Rifaximin Outcomes in Cirrhosis - Malik, Sara; Aziz, Hassan; Ullah, Nadeem; Raza, Anjum; Siddiqui, Huzaifa Nazir; Khalid, Romaisa (Pakistan Journal of Health Sciences, 2024)
Rifaximin has emerged as a new primary intervention for the treatment and management of hepatic encephalopathy in cirrhosis patients. Objective: To evaluate the efficacy of long-term rifaximin therapy and its clinical effects on hepatic encephalopathy in patients with liver cirrhosis. Methods: A retrospective cohort study was conducted in the Hepatology and Medicine Department of Bakhtawar Amin Hospital, Multan, from May 2022 to May 2024. A total of 100 liver cirrhosis patients were selected for the study by consecutive sampling. The patients were divided into two groups: the rifaximin group, including 50 patients who were administered rifaximin for 6 months at this hospital, and the control group, including 50 patients who were not administered rifaximin. The primary end point of our analysis was to assess the effectiveness of long-term rifaximin therapy. Results: The baseline serum ammonia was 105 (60-296) μg/dL in the rifaximin group, which decreased to 83 (33-152) μg/dL after 14 days and 83 (44-190) μg/dL after 60 weeks (p=0.001). Adverse effects of rifaximin were presented in one patient (2%) in the form of diarrhea only. The patients with stents smaller than 8 mm had pretreatment ammonia of 100 (60-182) μg/dL and 65 (42-145) μg/dL post-treatment (P=0.040). Conclusions: Rifaximin was an effective and safe treatment regimen for the long-term treatment of hepatic encephalopathy in patients with liver cirrhosis. It reduces the serum ammonia levels and prevents E. coli infections, increasing survival. Ineffective rifaximin treatment was associated with portosystemic shunt diameter ≥ 8.